A New Independent Social Innovation Model - Ochilova Bakhti Muradovna (Zien Journals, 2022)
In this article, protection of the rights and legal interests of women in the society of Uzbekistan, increasing their economic, social and political activity, providing vocational training and employment, wide involvement in entrepreneurship, social support of needy women, ensuring gender equality the ongoing reforms are highlighted
Keywords: Priority of human interests; healthy and happy life; respect for women; interest-free education loans